New Media: Challenges and Opportunities for Brahui Journalism in Balochistan. - Niaz, Dr. Babrak; Dr. Allauddin; Baloch, Dr. Muhammad Fahim; Chhachhar, Dr. Abdul Razaque (Al-Burz, 2020)
This paper attempts to shed light on Brahui Journalism its geneses and challenges it faces in the era of contemporary technological advancements. Globally new media is replacing traditional way of communication. The reach and impact of new media is far stronger and long lasting than traditional media. Brahui language newspapers and magazines are facing hardships to use and adopt alternate media platforms. Lack of resources and less technological and IT skills are hurdles in this transition. The newspapers published in Brahui language completely depends on government advertisements in the absence of wellestablished private sector. The owners of the newspapers are bound to follow government policies in every aspect, therefore journalists want to switch to new media with prime objective to highlight contemporary social, political, cultural and religious issue of Balochistan and to find better revenue generating opportunities to decrease dependency on government advertisements.